2013
DOI: 10.1002/cjce.21788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liquid viscosity on hydrodynamics and bubble behaviour of an external‐loop airlift reactor

Abstract: The effect of liquid viscosity on hydrodynamics and bubble behaviour of an external-loop airlift reactor within air-water system were studied by an electrical conductivity probe. Carboxyl methyl cellulose (CMC) was used to change liquid viscosity (1.00-51.25 cP). Gas holdup increased with superficial gas velocity increasing, as well as bubble Sauter diameter and bubble rise velocity. With liquid viscosity increasing, average gas holdup increased first then decreased, while bubble Sauter diameter was opposite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The present state of the art of correlations [22][23][24][25][26][27][28] predicting the gas holdup in air-water 1 glycerol systems at U G 5 0.05 m/s is summarized in Figure 2. Except for Sotelo et al, 25 a reduction of the gas holdup with increasing liquid viscosity was observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present state of the art of correlations [22][23][24][25][26][27][28] predicting the gas holdup in air-water 1 glycerol systems at U G 5 0.05 m/s is summarized in Figure 2. Except for Sotelo et al, 25 a reduction of the gas holdup with increasing liquid viscosity was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Except for Sotelo et al, 25 a reduction of the gas holdup with increasing liquid viscosity was observed. [22][23][24][25][26][27][28] Apart from the available correlations, there are some controversial reports on the effect of the liquid viscosity on the gas holdup. 19,[29][30][31][32] An increase of gas holdup was found at low liquid viscosity l 3-4 mPa-s, a decrease at moderate viscosity l 5 3-11 mPa-s and roughly constant gas holdup at a higher viscosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of gas bubble is influenced by the physical properties of system, especially the viscosity of slag phase. 21) Therefore, this difference would be caused by the high viscosity of slag. When the gas flow rate increased to 300 NmL/min and higher, the difference in the gas bubble volume between the two systems became more marked.…”
Section: Resultsmentioning
confidence: 99%
“…A single bubble rising in a quiescent (or stagnant) liquid pool has been characterized by a number of previous studies. For instance, Luther et al [15], Cieslinski and Mosdorf [16], Ohta et al [17], and Wu et al [18] investigated the behavior of single bubble in the airlift reactor. Bunner and Tryggvason [19], Lu and Tryggvason [20], and Ziegenhein and Lucas [21] observed the characters of bubbles in vertical bubbly flow.…”
Section: Introductionmentioning
confidence: 99%